Electrochemical impedance spectroscopy as a tool to estimate thickness in PB films - Gimenez-Romero, D.; Bueno, Paulo Roberto [UNESP]; Castano, C.; Gabrielli, C.; Perrot, H.; Garcia-Jareno, J. J.; Vicente, F. (Elsevier B.V., 2006)
The analysis of the faradaic impedance of electroactive films provides a characteristic point from which it is possible to estimate the thickness of thin films. Thus, electrochemical impedance spectroscopy was used in this paper as a fast and easy technique to estimate this thickness. The proposed method was checked on PB films. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: Prussian blue; electrochemical impedance spectroscopy; thickness